2009
DOI: 10.4103/0253-7176.53308
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical, Neurochemical, and Neurodevelopmental Basis of Obsessive-Compulsive Symptoms in Schizophrenia

Abstract: The prevalence of the obsessive-compulsive symptoms in schizophrenia (OCSS) appears to be higher than that expected on the basis of comorbidity rates. Review of brain abnormalities in schizophrenia and obsessive-compulsive disorder (OCD) reveals involvement of similar regions namely the frontal lobe, the basal ganglia, the thalamus, and the cerebellum, in both the disorders. Neurodevelopmental etiopathogenesis has been proposed to explain schizophrenia as well as OCD. Significant overlap in neurotransmitter dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 89 publications
(141 reference statements)
1
6
0
Order By: Relevance
“…Unstable prefrontal glutamatergic system with hyperglutamatergic orbitofrontal (OFC) and hypoglutamatergic dorsolateral prefrontal (DLPFC) regions has been theorized to be the pathophysiology behind the schizo-obsessive disorder. 11) Similar glutamate mediated degenerative process involving the DLPFC along with striatal circuits would be resulting in the symptom presentation in our cases.…”
Section: Discussionsupporting
confidence: 57%
“…Unstable prefrontal glutamatergic system with hyperglutamatergic orbitofrontal (OFC) and hypoglutamatergic dorsolateral prefrontal (DLPFC) regions has been theorized to be the pathophysiology behind the schizo-obsessive disorder. 11) Similar glutamate mediated degenerative process involving the DLPFC along with striatal circuits would be resulting in the symptom presentation in our cases.…”
Section: Discussionsupporting
confidence: 57%
“…The association between genes affecting the glutamatergic, dopaminergic, and serotoninergic neurotransmission could suggest that neurotransmitters overlap within the cortico-striatal-thalamo-cortical circuit (CSTC) in both OCD and schizophrenia conditions [57]. Brain abnormalities as unveiled by imaging studies may involve common regions in schizophrenia and OCD: the frontal lobe, the basal ganglia, the thalamus, and the cerebellum [59]. Functional neuroimaging studies have shown reduced neural activation in the dorsolateral prefrontal cortex (DLPFC) and right caudate of schizophrenia patients with and without OCS compared to healthy controls [60,61].…”
Section: Genetic Findings Of Ocd In Schizophrenia: Relevance For Sero...mentioning
confidence: 99%
“… 96 , 97 It was strongly suggested that the serotoninergic antagonism of second-generation antipsychotics, which results in an imbalance between serotoninergic and dopaminergic system, contributes to this side effect; 98 alteration or dysfunction of glutamatergic and dopaminergic neurotransmission might also be involved. 99 , 100 Patients with comorbid OCS in schizophrenia are generally suffering from more neurocognitive impairment, more severe psychosis, and treatment resistance. 101 , 102 …”
Section: Benefits and Risks Of Antidepressants For Patients With Schimentioning
confidence: 99%